THE IMPLEMENTATION OF COGNITIVE STRATEGY INSTRUCTION IN WRITING (CSIW): A CLASSROOM ACTION RESEARCH - Muhyiddin Aziz; Eda Maaliah (Humaniora Scientia, 2018)
There are some important aspects in teaching English especially writing skill such aslecturers as the mediator on teaching and learning process, the methods as the way totransfer the knowledge and train the skill, and the goal of the study as the aim of teaching. Allthe targets are based on how well they colaborate all aspects during the process of teachingand learning. Cognitive Strategy Instruction in Writing (CSIW)was chosen to know theeffectiveness, streghts, and weaknesses in improving the writing skill of the Second Semesterof English Study Program of Madiun State Polytechnic in the Academic Year of 2017/2018.The qualitative and quantitative data were used in this research. Qualitative data were takenfrom the scores of the pre-test of twenty eight studemnts from A class and all cycles of theresearch. The qauntitative data were taken through the observation, interview, andquestionnaire. Based on the discussions and conclusions, Cognitive Strategy Instruction InWriting (CSIW) is recomended to improve the writing skill of the Second Semester of EnglishStudy Program of Madiun State Polytechnic in the Academic Year of 2017/2018.Â Â Keywords: CAR, writing skill, CSIW